Service-oriented simulation using web ontology. (1st January 2012) - Bell, David; de Cesare, Sergio; Lycett, Mark; Taylor, Simon J.E.; Mustafee, Navonil
Commercial-off-the-Shelf (COTS) Simulation Packages (CSPs) have proved popular in a wider industrial setting. Reuse of Simulation Component (SC) models by collaborating organisations or divisions is restricted, however, by the same semantic issues that restrict the inter-organisation use of other software services. Semantic models, in the form of ontology, utilised by a web-service-based discovery and deployment architecture provide one approach to support simulation model reuse. Semantic interoperation is achieved using domain-grounded SC ontology to identify reusable components and subsequently loaded into a CSP, and locally or remotely executed. The work is based on a health service simulation that addresses the transportation of blood. The ontology-engineering framework and discovery architecture provide a novel approach to inter-organisation simulation, uncovering domain semantics and providing a less intrusive mechanism for component reuse. The resulting web of component models and simulation execution environments present a nascent approach to simulation grids.